A fungal effector and a rice NLR protein have antagonistic effects on a Bowman–Birk trypsin inhibitor. Issue 11 (4th July 2020) - Zhang, Chongyang; Fang, Hong; Shi, Xuetao; He, Feng; Wang, Ruyi; Fan, Jiangbo; Bai, Pengfei; Wang, Jiyang; Park, Chan‐Ho; Bellizzi, Maria; Zhou, Xueping; Wang, Guo‐Liang; et al.
Summary: Bowman–Birk trypsin inhibitors (BBIs) play important roles in animal and plant immunity, but how these protease inhibitors are involved in the immune system remains unclear. Here, we show that the rice ( Oryza sativa ) BBI protein APIP4 is a common target of a fungal effector and an NLR receptor for innate immunity. APIP4 exhibited trypsin inhibitor activity in vitro and in vivo . Knockout of APIP4 in rice enhanced susceptibility, and overexpression of APIP4 increased resistance to the fungal pathogen Magnaporthe oryzae . The M. oryzae effector AvrPiz‐t interacted with APIP4 and suppressed APIP4 trypsin inhibitor activity. By contrast, the rice NLR protein Piz‐t interacted with APIP4, enhancing APIP4 transcript and protein levels, and protease inhibitor activity. Our findings reveal a novel host defence mechanism in which a host protease inhibitor targeted by a fungal pathogen is protected by an NLR receptor.